Patents prospective study related to vaccines against SARS-CoV-2 - Bezerra, Ellen Aparecida Guimarães (2021)
Pandemic of COVID-19 has triggered intense global research activity to develop vaccines as a strategy against SARS-CoV-2. To stimulate technological innovation and evaluate the landscape protection of processes and products related to this area, the aim of this research was to realize a prospective study of related patents to vaccines against SARS-CoV-2. Searches were carried out in the patent databases: EPO, USPTO and INPI using the descriptors "SARS-CoV-2" and "vaccine" or "SARS-CoV-2" and "vaccine", being included vacines patents and/or components that contained the International Patent Classification (IPC) codes: A61K39/00, A61K39/12 and A61K39/215. Exclusion criteria were duplicates in the same database. A total of 62 patents were found, 51 at the EPO, 11 at the USPTO and none at the INPI. The volume of patents found is considerable given that the disease appeared in December 2019. In addition to complete vaccines, carriers, peptides with oligonucleotides, adjuvants, cells, epitopes, proteins, recombinant viruses and artificial genes were also patented. The applicant companies are 61.3% patents applied for by Chinese companies, 16.1% by US companies, and 22.6% by companies based in other countries. The inventors nationalities with expressiveness in patent filings were represented by Russians and Chinese, respectively. With the survey it was possible to verify that the pandemic has significantly broadened the gaze of the scientific community for investigations that provide a solution to the disease, generating high production of scientific and technological knowledge that culminated in the filing of patents related to vaccines against SARS-CoV-2.